Evaluation of Accounting System on Inventory Management at General Store PT. Equiport Inti Indonesia Site Bitung - Lesa OCTARI; Raykes Hinrich TUERAH; Jery LINTONG (Journal of Governance, Taxation and Auditing, 2022)
This study discusses the evaluation of the accounting system for inventory management at PT. Equiport Inti Indonesia Bitung site. This study aims to find out how the accounting system for inventory management at PT. Equiport Inti Indonesia Site Bitung, to be precise, is the warehouse section as a place to store supplies. The type of research used in this research is descriptive qualitative. The data collection technique used is primary data, namely the results of interviews and secondary data, namely books, journals, theses and the internet, with data collection techniques using observation, interview documentation and literature study. The resource persons are assistant managers and staff working in the accounting department. The results showed the difference between the accounting records carried out by the warehouse function and the accounting function and the amount of physical inventory at the time of stock taking at the end of each month. Therefore, it is necessary to make improvements to the accounting system for inventory management so that the system implemented can benefit the effectiveness of the company’s employee performance. The accounting system and internal control at PT. The Inti Indonesia Bitung Equiport site is considered very weak. The company needs to function correctly and as a shopkeeper, such as an accuracy in recording Request Orders into the Stock Card so that the records made by the warehouse and accounting functions can be appropriate.